Razrabotka sovremennoj kompleksnoj tekhnologii kontrolya v vidakh edinoborstv - Sanosyan, Kh. A.; Musaelyan, S. L.; Agamyan, M. G.; Kirakosyan, K. Zh. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
There are widely used exercises with throws of wrestling dummies for the control of the level of special preparedness (SP) in the single combats (Greek-Roman and Freestyle Wrestling, Judo and Sambo). The complex technology of the control of the special preparedness was offered to application in the single combats, including both traditional, and the technologies developed and modified by authors with the purpose of increase of information of the test tasks and the efficiency of the correction of a training process. The calculation of parameters of the special endurance concerns to the last in an operative range of output and capacity of mechanisms of energy support and sources making them - substrata. The formula of training (algorithm), which should be based on modern technologies of planning and be their component that will allow to operate training process on more high level, is offered in the article.